2010
DOI: 10.18632/oncotarget.176
|View full text |Cite
|
Sign up to set email alerts
|

NSP 5a3a: A Potential Novel Cancer Target in Head and Neck Carcinoma

Abstract: AbstrAct:NSP 5a3a along with three other distinct though similar splice variants were initially identified corresponding to locus HCMOGT-1 on chromosome 17p11. Subsequent investigation, elucidated NSP 5a3a's potential involvement in cellular processes such as ribosome biogenesis and rRNA processing by validating NSP 5a3a's novel interaction with B23 and ribonuclear protein hnRNP-L possibly implicating NSP 5a3a's involvement in cellular activities such as RNA metabolism and processing [4]. In this preliminary i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…64 Although TP73 was found to induce expression of Atg5 and Atg7, the Tp73 knockdown increased Uvrag expression levels, suggesting that by binding to a region upstream of the Uvrag transcriptional start site, TP73 represses its expression via recruitment of histone deacetylases. 62,66 ΔNp63α was shown to activate Atm transcription, 65 thereby contributing to ATM-TSC2-mTORC1-dependent autophagic pathway. 55 We have previously reported that the endogenous p-ΔNp63α, but not non-p-ΔNp63α, induced some autophagic features through an indirect stabilization of LKB1 levels and was likely to activate the ATM-TSC2-mTORC1 signaling in SCC cells upon cisplatin exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…64 Although TP73 was found to induce expression of Atg5 and Atg7, the Tp73 knockdown increased Uvrag expression levels, suggesting that by binding to a region upstream of the Uvrag transcriptional start site, TP73 represses its expression via recruitment of histone deacetylases. 62,66 ΔNp63α was shown to activate Atm transcription, 65 thereby contributing to ATM-TSC2-mTORC1-dependent autophagic pathway. 55 We have previously reported that the endogenous p-ΔNp63α, but not non-p-ΔNp63α, induced some autophagic features through an indirect stabilization of LKB1 levels and was likely to activate the ATM-TSC2-mTORC1 signaling in SCC cells upon cisplatin exposure.…”
Section: Discussionmentioning
confidence: 97%
“…Elucidation of the functional implications of this bivalent regulation may lead to a better understanding of the miRNA-mediated cellular stress response to cisplatin exposure specifically and to chemotherapeutic drugs in general. [66][67][68][69][70][71][72][73] Distinct members of autophagic flux exert their specific roles through physical and functional interactions between each other and components of the apoptotic and cell cycle arrest machinery; thereby, the final outcome of cellular response to stress might lead to a variety of choices. 51,54,74 During chemotherapy-and UV (UV)-induced apoptosis, the UV-resistanceassociated gene product, UVRAG, activates the BECN1/ phosphatidylinositol-3-kinase III (PI3K III) complex, which promotes autophagosome formation.…”
Section: Methodsmentioning
confidence: 99%
“…SPECC1 message was also detected at moderate or higher levels in canine lung adenocarcinomas and various sarcomas ( Figure S1E), but was negative (n = 1), weak (n = 4; 0. 34 with characteristic morphology ( Figure S1F), but found no SPECC1 expression. Given these encouraging results, the distribution of SPECC1 in other normal somatic tissues was investigated further, revealing strong expression in the central nervous system (CNS), bone marrow and urinary bladder, and moderate expression in pituitary gland, small and large intestine, and skeletal muscle ( Figure 1C, upper).…”
Section: Additional Proteins From Dh82 Cells With Enhanced Testis Ementioning
confidence: 99%
“…Fusion partner with PDGFRβ in myelomonocytic leukemia 33 High expression in brain and bone marrow precludes use as antigenic target Pro-apoptotic gene in head and neck carcinoma lines 34,35 As a key regulator of Aurora-A kinase, which controls spindle assembly and function during mitosis, 52,53 TPX2 expression in the DH82 line might simply result from the fact that, at any given time, a substantial fraction of cultured cells are undergoing division, and similarly robust expression might not be observed in clinical HS specimens. Analysis of biopsies by qPCR, however, showed strong and FIGURE 2 Expression of TPX2 message (relative to RPL8) in DH82 cells and the indicated canine tissues and tumours, as determined by quantitative PCR (qPCR) analysis.…”
Section: Specc1mentioning
confidence: 99%
“…In this issue of Oncotarget, D'Agostino and Giordano investigate the effect of over-expressing NSP5a3a in head and neck squamous cell carcinoma (HNSCC) cell lines [4]. HNSCC is one of the 10 most common cancers worldwide and the overall survival rate for HNSCC is still low even with the latest innovations in both basic and clinical research [5].…”
mentioning
confidence: 99%